THE EFFECT OF BRAINSTORMING METHODE ON CRITICAL THINKING SKILLS AT LEARNING SCIENCE FOR PRIMARY SCHOOL - Marfilinda, Riri; Selni Septia Ningsih; Ade Irma Suryani; Elva Zuleni (Cerdas Proklamator, 2023)
This research is motivated by critical thinking skills of students in understanding the subject matter delivered by the teacher which is still low due to a less varied learning process. The ability of students to understand the concepts of the material being taught is still not able to develop new knowledge actively so that students have not been able to develop critical thinking skills in the learning process. This study aims to determine the effect of using the brainstorming method on student’s' critical thinking skills in science learning in Class IV SDN 11 Tanjung Medan. The population of this research is the fourth grade students of SDN 11 Tanjung Medan and a nonequivalent control group design. The data collection in this study was using a critical thinking skill test in the form of 25 objective questions, the data obtained were analyzed using the t test. Based on the results of hypothesis testing with t-test, the data obtained by the value of tcount = 3.661 with a difficulty level of 5% with the test criteria if tcount> ttable then the hypothesis or H1 is accepted and H0 is rejected. The t-test value obtained is tcount = 3.661 > ttable = 2.074. From the results of the study, it was proven that "The critical thinking skills of students who learn to use the brainstorming method are higher than students who do not learn to use the brainstorming method in science learning at SDN 11 Tanjung Medan.